Relaciones internacionales y estrategias de comunicación de la España de Franco ante la coyuntura de 1956 - Eiroa San Francisco, Matilde (Historia y Comunicación Social, 2007)
50 years ago coincided in different parts of our world, events which pointed out a phase in the Cold War. 1956 signed the beginning of the disjointed of the blocks with the confluence of several crack in the Bipolar World Order: the end of the Stalinism in the USRR, the Hungarian revolution, the polish revolt, the Channel of Suez crack or the independence of Morocco. These events were not unnoticed in the Spaniard foreign policy, over all the grant of sovereignty to Morocco, priority to the government around which they activated an integral mechanism of communication in order to have an appropriate diffusion.